Pengaruh Kegiatan Keterampilan ART Therapy untuk Mengurangi Stres Pada Lansia di Yayasan Budi Sosial Batam - Muhammad Putra Hidayat; Maria Lepang Angelina Koten; Virisya Chumaerotusyifa; Devi Lamtiur Gultom; Elisabeth Nona Yunita (Jurnal Abdimas ADPI Sains dan Teknologi, 2023)
Elderly is a life process that will be passed by every human being. Where the elderly age declines and changes that occur physically and mentally. Elderly individuals will be very vulnerable to health problems, including stress caused by changes in old age life. The stress will certainly appear both physically, psychologically, and socially. Art therapy is one of the right ways to express emotions through pictures and colors. This activity will certainly please the feelings of the elderly. The purpose of this activity is to determine the effect of art therapy on the stress experienced by elderly patients while they are at the nursing home foundation. This activity was attended by 7 participants who were willing and in accordance with the inclusion criteria made by the activity implementers and carried out on April 14, 2023. The method of this activity was lectures and demonstrations. This activity is expected to be useful for the elderly and of course it can be an alternative for nursing home foundations to prevent/reduce stress on the elderly and of course it can improve the welfare of the elderly in social charity foundations.